Monitoring vertical displacement of reinforced concrete beam by digital processing technology / Syahrul Fithry Senin... [et al.] - Senin, Syahrul Fithry; Rohim, Rohamezan; Yusuff, Amer; Fazlan Rozli, Mohd Ikmal; Ahmad, Juraidah (Universiti Teknologi MARA, Negeri Sembilan, 2018)
Structural Health Monitoring (SHM) is a crucial scope of work in civil engineering specifically on monitoring the in-service and ageing coastal bridge deck concrete structure serviceability and limit state status performance. One of the possible natural process that pose detrimental effects to such structure performance monitoring is the steel rebar pitting corrosion problem. Progressive pitting corrosion process on the certain steel rebar area in low quality of concrete cover due to chloride ingression will cause local premature damage the steel rebar which obviously affect the serviceability performance of the structural element, i.e. displacement. However, the available displacement monitoring methods become an issue when it comes to engineering practicality and costs considerations. Therefore, the purpose of this study is to monitor and analyze the vertical displacement of an undamaged and damage reinforced concrete beam using the digital signal processing technology, Digital Image Correlation, (DIC) that use Sony camera and MATLAB scripts, and compared to a traditional method, Linear Variable Displacement Transducer (LVDT) at two points bending tests setup. It was concluded, that the quantified displacement for corrosion-damage RC via DIC method is higher than the normal reinforced concrete beam by 2 to 46 percent of error to LVDT measurements. Based on two tailed paired t-test analysis, DIC method was concluded to be as good as the LVDT method of measuring the beam’s displacement. The developed method has the potential implementation on monitoring the any beam deflection on current real civil engineering related projects.